Alu SINE analyses of 3, 000-year-old human skeletal remains: a pilot study. Issue 1 (December 2016) - Kothe, Maximilian; Seidenberg, Verena; Hummel, Susanne; Piskurek, Oliver
Abstract Background As Short Interspersed Elements (SINEs), human-specificAlu elements can be used for population genetic studies. Very recent inserts are polymorphic within and between human populations. In a sample of 30 elements originating from three differentAlu subfamilies, we investigated whether they are preserved in prehistorical skeletal human remains from the Bronze Age Lichtenstein cave in Lower Saxony, Germany. In the present study, we examined a prehistoric triad of father, mother and daughter. Results For 26 of the 30Alu loci investigated, definite results were obtained. We were able to demonstrate that presence/absence analyses ofAlu elements can be conducted on individuals who lived 3, 000 years ago. The preservation of the ancient DNA (aDNA) is good enough in two out of three ancient individuals to routinely allow the amplification of 500 bp fragments. The third individual revealed less well-preserved DNA, which results in allelic dropout or complete amplification failures. We here present an alternative molecular approach to deal with these degradation phenomena by using internalAlu subfamily specific primers producing short fragments of approximately 150 bp. Conclusions Our data clearly show the possibility of presence/absence analyses ofAlu elements in individuals from the Lichtenstein cave. Thus, we demonstrate that our method is reliably applicable for aDNA samples with good or moderate DNA preservation. This method will be very useful for further investigations with moreAlu loci and larger datasets. Human population genetic studies and other large-scale investigations would provide insight intoAlu SINE-based microevolutionary processes in humans during the last few thousand years and help us comprehend the evolutionary dynamics of our genome.